Factors Related to Anemia in Pregnant Women at the Kotaraja Health Center - Rahim, Muh. Taufik Rizal; Adimuntja , Natalia P.; Pamangin , Lisda Oktavia M.; Tingginehe, Rosmin Mariati; Tambing, Yane; Tuturop, Katarina; Hasmi, Hasmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Anemia poses a growing health concern within the community, particularly among pregnant women who require special attention due to increased nutritional needs for fetal development. The aim of this research is to identify the factors associated with anemia among pregnant women at the Kotaraja Health Center. This type of research is analytical observation with a cross-sectional approach. The study sample consisted of 156 individuals selected from a population of 202. The study utilized simple random sampling as The sampling technique. The results indicated a significant association between age and anemia in pregnant women P-value (0.035), nutritional status P-value (0.004), the ANC frequency P-value (0.009), and infection diseases P-value (0.035). However, the parity variable showed no significant association with anemia in pregnant women, as indicated by a p-value (0.097). In conclusion, age, nutritional status, frequency of ANC visits, and infection diseases all have a significant association with the incidence of anemia in pregnant women.